Socialists May be Christians; Christians Must be Socialists. Karl Barth Was! - Rumscheidt, Hans Martin (Toronto journal of theology, 2001)
The title of my essay includes a statement by a Christian in Germany who wished to specify how he understood his personal theological existence. Adolf Grimme spoke those words in 1946, in the aftermath of Germany's defeat in World War II. Hunger was widespread, material deprivation extensive, and untold human tragedy weighed down a people dehumanized by the idolatry of National Socialism. A collective shouldering of the burden of reconstructing Germany gave the word "socialism" a powerful appeal. Whether it was infused with a Christian or a Marxist meaning was secondary to the vision of freeing this concept from the Nazis' barbaric distortion of it. Grimme belonged to the tradition known as "Religious Socialism;" it landed him in prison during the Hitler years. He envisioned the overturning of those social conditions that are based in capitalistic private ownership. In that aim he was as unequivocal as Hermann Kutter, the Swiss Religious-Socialist of the early part of the twentieth century, who, in 1903, had published his manifesto Sie müssen!They Must! Grimme's imperative "must" is derived from that work and expresses precisely what Kutter's conclusion had been: Christians must be Socialists. It is historically illuminating that in 1946 the reaction of Christians to Grimme was quite mild. Kutter, on the other hand, reaped anger. Today, in the context of the churches' and the Western theological guild's accommodation with neo-liberal capitalism, professing that as a Christian one must be a Socialist is met with the same anger.